(3ecGaMI GdaTd GdeOQSjs - (3ajGfjf, HjGQs ((3HjQhJs (3OGQ GdaGQGHjs, 2009)
(3jYQV GdeDda deSCdI GdcaGM VO GdaTd GdeOQSj eMOOkG hVhM GdOhQ GdPj jecf ddCgd hGdCSGJPI Cf jdYHhg deSGYOI GdJdGejP GdPjf jYGfhf ef UYhHI aj GdJYde(B. (3aGHJcGQg jcef aj LeYg dcd GdNUGFU GdegeI dYed GdCSJGP GdOGYe ceG aj GbJQGMg dCLhHI hGbYjI hWQb JONd bO JSGYO GdJdGejP GdPj jYGfhf ef UYhHI aj GdJYde(B. (3eTOOG Ydi GdUYhHGJ GdYOI GdJj hGLggG GdCSGJPI hNGUI GdOGYejf efge(B. (3jDcO gPG GdeDda Ydi CgejI GdJONd Ydi GdeSJhi GdeDSSj hGdJQHhj ceG GdTNUj hPdc EPG CQOfG GdcaGM HaYGdjI VO GdaTd GdeOQSj(B. (3agh jYQV CjVG dJWhQ GdeTQhY GdJQHhj hjHjf CgejI GdJYGhf eY LejY GdTQcGA aj GdYed(B. (3hCNjQG aEfg jbqhe aYGdjI GdOYe GdJQHhj(B. (3jgOa GdeDda Edi JhVjM hSGFd hCgOGa ELQGAGJ GdeSGYOI GdeJNPI JLGg GdJdGejP GdPjf jYGfhf UYhHI aj GdJYde(B. (3agh jJhLg Edi (B(" (3COJc (B" (3CSGJPI GdOYe GdJQHhj GdcGed COJc (B) (3MjK jDef gPG GdeDda CjVG eSGYOI aYGdI dcd ef jhGLg UYhHGJ aj JOQjS Wad eG MJi Cf eOQSj GdUaha GdGYJjGOjI ceG GdCgd SjLOhf CfaSge aj ehbY (B" (3GdeYGhf (B" (3ajdYHhf eQGQG OhQ Gd` COJc(B. (3SjLOhf aj gPG GdeDda eQTOG fGaYG, jbOe CeKdI YOI hjDef eSGYOI aYGdI dChdGOge(B.s
(3GdfhY (B: (3cJGHs
Keywords: Redoublement Scolaire; School failure; (3GdQShH GdeOQSjs